Usage level of educational technologies of students at electronic computer department in technical high school - (:unkn) unknown (SILA SCIENCE, 2012)
The most valuable resource of a society that enables it to survive is human power. The education and employment of this resource not only shows the difference of a society from the others, but renders a healthy interaction within the society. This difference is only possible with education. There is yet no consensus about the concept of education. When we look at education within this framework, the factor which will provide the biggest contribution to the development of the country is the vocational, technical education. The vocational, technical education must serve the society more and more every single day in order to provide for the limitless needs of humans. Although the fact that vocational, technical education should not ultimately educate people into only one unique mold does not seem to agree to the other concepts of education, vocational improvement will only be possible with the employee who has acquired good vocational background, who can speculate the future and who can present his/her speculation with scientific research. These qualifications are only possible when the individual gets a good vocational education. The research has been applied as choosing with the simple random sampling method in Istanbul. Total of 242 students were asked about the use of educational technologies, use of information technologies, using the skills of the internee and requirements, difficulties on educational technology. It has been seen that students use educational technologies and informational technologies at basic level and not enough using the skills of the internet of students.
Keywords: Educational technology; Use of the educational technology; Use of the internet